Reductions in Childhood Pneumonia Mortality After Vaccination in the United States (2023)
BACKGROUND: We aim to estimate the magnitude of the reduction in pneumococcal pneumonia and meningitis mortality after the mass introduction of pneumococcal conjugate vaccine (PCV)7 and PCV13 in children in the United States. METHODS: We assessed the trends in mortality rates from pneumococcal pneumonia and meningitis, in the United States between 1994 and 2017. We fitted an interrupted time-series negative binomial regression model (adjusted by trend, seasonality, PCV7/PCV13 coverage, and H. influenzae type b vaccine coverage) to estimate the counterfactual rates without vaccination. We reported a percent reduction in mortality estimates relative to the projected no-vaccination scenario, using the formula 1 minus the incidence risk ratio, with 95% confidence intervals (CIs). RESULTS: Between 1994 and 1999 (the prevaccination period), the all-cause pneumonia mortality rate for 0-1-month-old children was 2.55 per 100,00 pop., whereas for 2-11 months-old children, this rate was 0.82 deaths per 100,000 pop. During the PCV7-period in 0-59-month-old children in the United States, the adjusted reduction of all-cause pneumonia was 13% (95% CI: 4-21) and 19% (95% CI: 0-33) of all-cause meningitis For PCV13, the reductions in this age group were 21% (95% CI: 4-35) for all-cause pneumonia mortality and 22% (95% CI: -19 to 48) for all-cause meningitis mortality. PCV13 had greater reductions of all-cause pneumonia than PCV13 in 6-11-month-old infants. CONCLUSIONS: The universal introduction of PCV7, and later PCV13, for children 0-59 months old in the United States was associated with decreases in mortality due to all-cause pneumonia.